1998
DOI: 10.1046/j.1365-2044.1998.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music on anaesthetists' psychomotor performance

Abstract: SummaryMany surgical patients are anxious while waiting to go to the operating theatre in spite of the best preparation with drugs, information and reassurance. It is possible that patients could be more comfortable if allowed a choice of activities before operations. The objective of this study was to find out how pre-operative patients might prefer to occupy their time. We distributed 200 questionnaires to elective surgery patients and 184 (92%) were available for analysis. Of the respondents, 54.1% wanted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Hawksworth et al . [5] tested the effect of music on performance of a perceptual‐motor task (rather than on patient monitoring) and found that music had no effect. We find no effect of music on abnormality judgements but strong improvements with music for trend judgements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hawksworth et al . [5] tested the effect of music on performance of a perceptual‐motor task (rather than on patient monitoring) and found that music had no effect. We find no effect of music on abnormality judgements but strong improvements with music for trend judgements.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hawksworth et al. [5] investigated the effect of silence, white noise, Pachelbel's Canon and self‐chosen music on anaesthetists' ability to perform a general manual control task and found no effect. Further evidence for the effect of music comes from surgery rather than from anaesthesia.…”
mentioning
confidence: 99%
“…54 A study of 12 anaesthetic trainees found no significant difference in psychomotor performance (testing numeric vigilance, tracking and reaction time) under four conditions (classical music, self-chosen music, white noise and silence). 55 The 24 non-anaesthetist participants in another study were able to judge trends in simulated patient monitoring more accurately while listening to music. 56 Despite this finding, participants reported a preference to work in silence.…”
Section: Musicmentioning
confidence: 99%
“…For example, in a survey by Hawksworth et al, the majority of staff interviewed had a negative opinion of music in the operating theatre. 3 Both the flight industry and military have also reported auditory stimuli as a cause of stress impacting performance. 46 However, the true effects of music and other auditory stimuli are still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…11, 12 Hawksworth et al confirmed this observation in anesthesiologists exposed to a variety of auditory stimuli. 3 …”
Section: Introductionmentioning
confidence: 99%